"One in four" with a mental health problem: the anatomy of a statistic. (22nd February 2012) - Ginn, Stephen; Horder, Jamie
Abstract : Despite a lack of supporting evidence, the claim that one in four people will have a mental health problem at some point in their lives is a popular one. Where does this figure come from, and why does it persist, ask Stephen Ginn and Jamie Horder